2013
DOI: 10.1177/2042018813476084
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic applications of melatonin

Abstract: Melatonin is a methoxyindole synthesized within the pineal gland. The hormone is secreted during the night and appears to play multiple roles within the human organism. The hormone contributes to the regulation of biological rhythms, may induce sleep, has strong antioxidant action and appears to contribute to the protection of the organism from carcinogenesis and neurodegenerative disorders. At a therapeutic level as well as in prevention, melatonin is used for the management of sleep disorders and jet lag, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 112 publications
(210 reference statements)
0
53
0
6
Order By: Relevance
“…Экзогенный мелатонин, принимаемый в вечернее время, стабилизирует работу супрахиазменных ядер гипоталамуса и обозначает точку отсчета для опре-деления субъективного темного времени суток, открывая «ворота сна» [20][21]. В ряде исследований было проде-монстрировано положительное влияние мелатонина на дневную сонливость, сокращение периода засыпания и количество ночных пробуждений, восстановление нару-шенной инициации сна у больных с ЦИ [22][23][24][25][26].…”
Section: нервно-психические расстройстваunclassified
“…Экзогенный мелатонин, принимаемый в вечернее время, стабилизирует работу супрахиазменных ядер гипоталамуса и обозначает точку отсчета для опре-деления субъективного темного времени суток, открывая «ворота сна» [20][21]. В ряде исследований было проде-монстрировано положительное влияние мелатонина на дневную сонливость, сокращение периода засыпания и количество ночных пробуждений, восстановление нару-шенной инициации сна у больных с ЦИ [22][23][24][25][26].…”
Section: нервно-психические расстройстваunclassified
“…In addition, physiological levels of melatonin were shown to stimulate multiple DNA repair systems and reduce the metastatic properties of human breast cancer cells (Sliwinski et al, 2007;. At pharmacologically relevant levels, melatonin decreased cell proliferation in a variety of cancer cell type, including cervical cancer, gliomas, and ovarian cancer, and has also been shown to induce apoptosis in specific cancer cell lines without cytotoxicity to any noncancerous cells (Kostoglou-Athanassiou, 2013;Rodriguez et al, 2013). To examine the tumorigenic effects of "light at night" in animal models, Blask and colleagues exposed rats with human breast cancer xenografts to one of six different intensities of light during their normal dark phase, ranging from total darkness to bright light, and reported a dose-related tumor growth rate and bloodmelatonin suppression, with more light at night corresponding to faster tumor growth rates and lower blood-melatonin levels .…”
Section: Circadian Disruption In Humans and The Melatonin Hypothesismentioning
confidence: 99%
“…In clinical, melatonin is commonly used for insomnia, and also applied in children with autism [23]. And experimental studies reported that melatonin treatment could attenuate sleep disorder without side effect [24]. In this paper, we discuss the effect of circadian dysregulation on physical and behavioral abnormalities.…”
Section: Introductionmentioning
confidence: 99%